The much anticipated marriage of cycling and transit. But how will it work? - Bachand-Marleau, Julie; Larsen, Jacob; El-Geneidy, Ahmed M. (My University, 2011)
In response to the environmental, economic and social costs associated with over-reliance on the automobile, planners and transportation professionals are promoting sustainable alternatives such as walking, cycling, and public transit, either as single modes or in combination. It has been argued that the marriage between cycling and transit presents opportunities for synergy by enlarging catchment areas of transit stations, while drawing in new users to both of these "green" modes. However, due to the marginality of this practice in North America, there is a shortage of reliable empirical studies in this area. The present research addresses this gap through an analysis of travel behavior and preferences related to cycle-transit integration (CT). An on-line survey was conducted in the region of Montréal, Canada during the summer of 2010. The questionnaire included a section on Montréal s public bicycle sharing system, BIXI, and its potential for integration with transit. We identify three current or potential CT users groups using a factor-cluster analysis: current parking bike-and-riders, BIXI users and car drivers. Bringing a bicycle on transit is the preferred form of integration; however, scenarios involving bicycle parking (or using a public bicycle) are likely to be used more regularly. In order to accommodate the greatest number of bicycletransit trips, measures facilitating parking at transit stops and those that enable bringing bicycles on board transit vehicles are recommended in tandem.
Keywords: Individualverkehr; Fahrradverkehr; ÖPNV; Fahrradmitnahme; Bike and Ride; Studie; Multimodalität; Nachhaltige Mobilität